TikTok and the transformation of social interaction - Feifei, Dong (Association for Scientific Computing Electrical and Engineering (ASCEE), 2025)
This research aims to investigate how TikTok, as a dominant social media platform among Generation Z, influences the transformation of social interaction in a digital context. Utilizing a quantitative approach supported by simulated survey data, this study explores the extent to which TikTok affects communication patterns, perceived changes in social behavior, and levels of social satisfaction. A total of 100 simulated responses from individuals aged 18 to 26 were analyzed using a structured questionnaire designed to capture the frequency of TikTok interaction, behavioral shifts in social engagement, and emotional outcomes related to online connectivity. The findings indicate a generally high level of platform engagement, with moderate indications of behavioral transformation and perceived digital fulfillment. Although the correlation between variables was weak in the simulated data, the study offers a nuanced understanding of how short-form video platforms like TikTok shape interpersonal dynamics, self-expression, and community belonging among young users. The primary contribution of this research lies in its early attempt to quantify the psychosocial effects of TikTok on Gen Z’s digital interactions through a structured, data-informed lens. By mapping the intersection of media consumption, behavioral change, and emotional gratification in a simulated environment, this study lays the groundwork for future empirical investigations and theoretical refinements in the field of digital media studies. It also adds to the emerging discourse on the sociocultural implications of algorithmically curated content in reshaping contemporary modes of social connectivity.